Perencanaan Pembelajaran PAI Berbasis Authentic Assessment dalam Mengukur Kompetensi Spiritual dan Sosial Siswa - Fairuz Azman; Ahmad Haikal; Lulu Agustini; Amelia Pangesti (Penerbit Minhaj Pustaka, 2026)
Lesson planning in Islamic Religious Education (IRE) plays a strategic role in developing students’ spiritual and social competencies in a holistic manner. However, assessment practices in IRE learning are still predominantly oriented toward cognitive aspects, so they have not fully measured the implementation of Islamic values in real-life contexts. Therefore, authentic assessment emerges as a relevant approach to support comprehensive evaluation in IRE learning. This study aims to examine the concept and strategies of IRE lesson planning based on authentic assessment in measuring students’ spiritual and social competencies. The research employs a library research method by reviewing scholarly sources, including academic journals, reference books, and previous studies related to authentic assessment and Islamic Religious Education. The data were analyzed through processes of reviewing, comparing, and synthesizing experts’ ideas. The findings indicate that authentic assessment provides a more comprehensive depiction of students’ development across cognitive, affective, and psychomotor domains through various techniques such as observation, performance assessment, projects, self-reflection, and portfolios. Thus, IRE lesson planning based on authentic assessment can be considered an effective strategy for achieving the holistic objectives of Islamic education. Abstraksi Perencanaan pembelajaran Pendidikan Agama Islam (PAI) memiliki peran strategis dalam mengembangkan kompetensi spiritual dan sosial peserta didik secara holistik. Namun, praktik penilaian dalam pembelajaran PAI masih cenderung berorientasi pada aspek kognitif, sehingga belum sepenuhnya mampu mengukur pengamalan nilai-nilai keislaman dalam kehidupan nyata. Oleh karena itu, autentik assessment menjadi pendekatan yang relevan untuk mendukung evaluasi pembelajaran PAI yang menyeluruh. Penelitian ini bertujuan mengkaji konsep dan strategi perencanaan pembelajaran PAI berbasis autentik assessment dalam mengukur kompetensi spiritual dan sosial peserta didik. Metode penelitian yang digunakan adalah kajian pustaka dengan menelaah jurnal ilmiah, buku referensi, dan penelitian terdahulu yang relevan. Data dianalisis melalui proses pengkajian, perbandingan, dan sintesis gagasan para ahli. Hasil kajian menunjukkan bahwa autentik assessment mampu memberikan gambaran komprehensif terhadap perkembangan peserta didik pada ranah kognitif, afektif, dan psikomotorik melalui teknik observasi, penilaian kinerja, proyek, refleksi diri, dan portofolio. Dengan demikian, perencanaan pembelajaran PAI berbasis autentik assessment efektif dalam mewujudkan tujuan pendidikan Islam yang holistik.